The SAGE handbook of counselling and psychotherapy - Feltham, Colin, 1950-; Hanley, Terry; Winter, Laura Anne (London: SAGE, 2017)
"This edition brings together comprehensively the fundamentals of counselling and psychotherapy for both trainees and experienced practitioners seeking expansion of their knowledge base. Focuses on the British society and multicultural profile for counseling and psychotherapy. This book tries to draw together as much consensual information, practice wisdom, mainstream theory, and pertinently challenging material as possible."--Provided by publisher.
Part 1. Counselling and psychotherapy in context. What are counselling and psychotherapy? -- What do people come to counselling and psychotherapy for? -- What are the training routes in counselling and psychotherapy? -- What are the training routes in counselling and psychotherapy? -- Part 2. Socio-cultural perspectives. Introducing socio-cultural perspectives : social justice and intersectionality -- Gender -- Disability -- Age -- Social class -- Sexuality -- Religion and spirituality -- Race, culture and ethnicity -- Part 3. Therapeutic skills and clinical practice. Introducing therapeutic skills and clinical practice : the 'basics' of therapeutic practice? -- The client-therapist relationship -- Assessment -- Risk : assessment, exploration and mitigation -- Formulation -- Using outcome and process measures -- Therapeutic beginnings -- Therapeutic middles -- Therapeutic endings -- Part 4. Professional issues. Introducing professional issues: therapeutic skills 'beyond therapy' -- Personal and Professional development -- Clinical supervision -- Leadership -- Confidentiality, note taking and record keeping -- Ethical codes and guidance -- Responding to complaints -- Client experiences -- Therapy and the law -- Mental health law -- Fundamentals of research -- Part 5. Theory and approaches. Introducing theory and approaches: singular models, combined approaches and alternative perspectives -- Adlerian therapy -- Jungian analytical psychology -- Attachment-based psychoanalytic psychotherapy -- Lacanian therapy -- Psychoanalytic therapy -- Psychodynamic psychotherapy -- Psychodynamic interpersonal therapy -- Acceptance and commitment therapy -- Cognitive therapy -- Compassion focused therapy -- Dialectical behaviour therapy -- Eye movement desensitisation and reprocessing (EMDR) -- Mindfulness based cognitive therapy -- Rational emotive behaviour therapy -- Ecotherapy -- Emotion-focused therapy -- Existential therapy -- Gestalt therapy -- Person-centred therapy -- Psychodrama -- Psychosynthesis therapy -- Narrative therapy -- Neuro-linguistic programming -- Personal construct counselling and psychotherapy -- Solution-focused brief therapy -- Cognitive analytic therapy -- Interpersonal psychotherapy -- Multimodal therapy -- Pluralistic therapy -- Schema therapy -- The skilled helper model -- Transactional analysis -- Part 6. Client presenting problems. Introducing client presenting problems: a critical approach to diagnosis and 'psychopathology' -- Introducing client presenting problems: a critical approach to diagnosis and 'psychopathology' -- Alcohol problems -- Anxiety and panic -- Bereavement -- Depression -- Counselling for drug-related problems -- Working with survivors of domestic violence -- Eating disorders -- HIV/AIDS -- Low self-esteem -- Medically unexplained symptoms (MUS) -- Obsessive compulsive disorder -- Personality disorders -- Phobias -- Post-traumatic stress disorder -- Sexual violence: rape and sexual assault -- The psychoses -- Relationship and sex problems -- Sexual abuse in childhood -- Managing stress -- Suicide and self-harm -- Part 7. Therapeutic Specialisms. Introducing therapeutic specialisms: continuing personal and professional development -- Counselling people labelled with Asperger Syndrome -- Working with disability -- Feminist therapy -- Gender, sexuality and relationship diversity therapy -- Working with homeless people -- Working with interpreters -- Working with refugees -- Coaching -- Working in further and higher education -- Working with the media -- Working with neuroscience and neuropsychology -- Private practice -- Working in primary care -- Short-term therapy -- Workplace therapy -- Counselling children -- Counselling young people -- Counselling older people -- Systemic family therapy -- Group therapy -- Relationship therapy -- Counselling by telephone -- Electronically delivered text therapies -- Wider uses of technology in therapy.
Previous edition: 2012.
Includes bibliographical references and index.
Keywords: Psychotherapy